TITLE: DIFFICULTIES STUDENTS FACE WHILE LEARNING ENGLISH AS A SECOND LANGUAGE IN UZBEK SCHOOLS - Abdullayeva Nigora Shavkatovna; A’zamjonova Maftuna Soxibjon qizi (TADQIQOTLAR.UZ, 2023)
Abstract This paper examines the challenges of learning English as a foreign language to Uzbek students. It highlights the lack of English exposure, grammar differences, shortage of qualified teachers, and limited resources as major hurdles.